Pembelajaran Matematika Guru dalam Kelas Multigrade di Sekolah Dasar: Studi Kasus di Sekolah Terpencil - Jusniani, Nia; Andayani, Andayani; Monariska, Erma (Lembaga Bale Literasi, 2026)
This study addresses four significant research gaps in the literature on multigrade teaching in Indonesia: (1) the absence of studies specifically examining mathematics teaching strategies in multigrade classrooms; (2) the methodological gap due to the dominance of quantitative descriptive approaches that cannot capture teachers' practical wisdom; (3) the contextual gap as international findings are not directly transferable to Indonesian remote school settings; and (4) the empirical gap in linking quantitative teacher shortage data with adaptive strategies developed by teachers in the field. Based on BPS Cianjur 2025/2026 data, the three research locations (Campakamulya, Pagelaran, and Leles sub-districts) have an average of only 7.9 teachers per school well below the Cianjur average of 10.2—confirming that multigrade teaching is a structural necessity, not a pedagogical choice. This study employs a qualitative approach with an instrumental case study design. Data were collected through in-depth interviews, classroom observations, and document analysis involving three experienced teachers in remote schools. Data analysis followed the Miles, Huberman, and Saldaña interactive model. The findings reveal five adaptive strategies developed independently by teachers without formal training: (1) adaptive classroom management with a tiered time-rotation system; (2) cross-grade cooperative learning and peer tutoring; (3) contextual differentiated instruction using local life contexts; (4) structured independent learning routines; and (5) local wisdom-based contextual adaptation integrating agricultural, economic, and cultural elements into mathematics. The novelty of this study lies in introducing the concept of 'multigrade teacher practical wisdom' as a category of professional knowledge constructed independently by teachers in the field, which has not previously been documented in Indonesian mathematics education literature.